Ultralow temperatures in a transport vessel: A dilution refrigerator to achieve 30 mK by continuous adsorption pumping - Batey, G.J.; White, J.P.; Duncan, W.D.; Simpson, A.F.; Mikheev, V.A. (Физика низких температур, 1997)
A novel design of dilution refrigerator (DR) is described for continuous operation inside a transport dewar with a neck diameter more than 51 mm. The time required for cooling the mixing chamber from room temperature to 30 mK is 3.5–4.5 h. Warming up to 300 K requires 0.5–1.0 h. The cooling power achieved is 40 at 100 mK. The DR is fitted with 6-mm line-of-sight access down to the mixing chamber. A distinguishing feature of this refrigerator is the absence of a conventional gas-handling system, which makes it easy to transport in a small car and quickly commission in a new laboratory within a few hours.